2019
DOI: 10.1128/aac.00528-19
|View full text |Cite
|
Sign up to set email alerts
|

Ceftazidime-Avibactam as Salvage Therapy for Infections Caused by Enterobacteriales Coresistant to Carbapenems and Polymyxins

Abstract: In this article, we report a case series of patients with infections caused by Enterobacteriales coresistant to carbapenems and polymyxins who were treated with ceftazidime/avibactam (CAZ-AVI) salvage therapy on a compassionate-use protocol. We enrolled 29 adult patients in 3 centers that had an infection due to a resistant microorganism and for whom the treatments available were considered ineffective, treated them with CAZ-AVI, and assessed clinical and microbiological cure at the end of treatment and all-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 12 publications
2
33
0
6
Order By: Relevance
“…Ceftazidimeavibactam (CAZ-AVI) is a novel synthetic β-lactamase inhibitor combination for a range of MDR Gramnegative infection [15,16], which was approved by the FDA in 2017. CAZ-AVI has been successfully used in patients with limited treatment options for complicated intra-abdominal infections and hospitalacquired, ventilator-associated pneumonia caused by CRE and other multidrug Gram-negative bacteria [17][18][19]. In the present study, the patient showed gradual improvement after treatment with CAZ-AVI and fosfomycin.…”
Section: Discussionsupporting
confidence: 49%
“…Ceftazidimeavibactam (CAZ-AVI) is a novel synthetic β-lactamase inhibitor combination for a range of MDR Gramnegative infection [15,16], which was approved by the FDA in 2017. CAZ-AVI has been successfully used in patients with limited treatment options for complicated intra-abdominal infections and hospitalacquired, ventilator-associated pneumonia caused by CRE and other multidrug Gram-negative bacteria [17][18][19]. In the present study, the patient showed gradual improvement after treatment with CAZ-AVI and fosfomycin.…”
Section: Discussionsupporting
confidence: 49%
“… 24 , 25 , 26 . The need to stay ahead of infection in the critically ill pushes clinicians towards a greater use of broad-spectrum antimicrobials in mechanically ventilated patients due to the difficulty in distinguishing the inflammatory phase of COVID-19 with the appearance of secondary infection [ 8 , 16 ]. Future studies are warranted to evaluate the changes in incidence of MDR infections during COVID-19 in Brazil with changes in antibiotic prescribing patterns.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ST16 KP has rarely been described harboring bla KPC , except for 2 isolates reported in Rio de Janeiro in 2008 and 2009 ( bla KPC-2 ) and 1 isolate in Israel. More recently, KPC-2–producing K. pneumoniae ST16 was detected in another teaching hospital also located in São Paulo [ 32 ]. This study thus depicts the largest outbreak caused by KPC-ST16 [ 16 , 17 , 33 ], which is a poorly characterized clone, in contrast to the successful ST11, ST258, ST307, or ST15 clones (also found in this study) [ 9 , 12 , 34–37 ].…”
Section: Discussionmentioning
confidence: 99%